Identification of Phakopsora pachyrhizi Candidate Effectors with Virulence Activity in a Distantly Related Pathosystem - Kunjeti, Sridhara G.; Iyer, Geeta; Johnson, Ebony; Li, Eric; Broglie, Karen E.; Rauscher, Gilda; Rairdan, Gregory J. (Frontiers in Plant Science, 2016)
Phakopsora pachyrhizi is the causal agent of Asian Soybean Rust, a disease that causes enormous economic losses, most markedly in South America. P. pachyrhizi is a biotrophic pathogen that utilizes specialized feeding structures called haustoria to colonize its hosts. In rusts and other filamentous plant pathogens, haustoria have been shown to secrete effector proteins into their hosts to permit successful completion of their life cycle. We have constructed a cDNA library from Phakopsora pachyrhizi haustoria using paramagnetic bead-based methodology and have identified 35 P. pachyrhizi candidate effector (CE) genes from this library which are described here. In addition, we quantified the transcript expression pattern of six of these genes and show that two of these CEs are able to greatly increase the susceptibility of Nicotiana benthamiana to Phytophthora infestans. This strongly suggests that these genes play an important role in P. pachyrhizi virulence on its hosts.